Simulation Study of a Single-Phase Induction Machine as a Water Pump System Utilizing Photovoltaic - Faturiansyah, Elfin; Syukriyadin, Syukriyadin; Hafid, Hafid (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
This paper presents a simulation study of using a single-phase induction machine as a solar PV powered water pump system equipped with Maximum Power Point Tracking (MPPT) on the boost converter. Inverters are used to convert DC voltage stored in batteries to drive single-phase induction machines. The simulation was carried out to analyze the system's performance in generating electrical power from solar panels and using it to operate the water pump. This research also considers variables such as fluctuations in sunlight intensity, as well as the dynamic response of induction machines and MPPT converters. From the simulation test results, it was found that the system as a whole will work well if it uses a radiation input that is more significant than 750 W/m2. The load in the form of a single-phase induction motor, which is inductive, influences variations in the output power produced by the solar PV at the boost converter.